2003
DOI: 10.1007/s00216-003-1843-z
|View full text |Cite
|
Sign up to set email alerts
|

Biosorption of cadmium, copper, lead and zinc by inactive biomass of Pseudomonas Putida

Abstract: The accumulation of Cd(II), Cu(II), Pb(II) and Zn(II) at mg L(-1) concentration levels by inactive freeze-dried biomass of Pseudomonas Putida has been investigated. These metals could be efficiently removed from diluted aqueous solutions. A contact time of 10 min was sufficient to reach equilibrium. The pH has a strong effect on metal biosorption and the optimal pH values were 6.0, 5.0-6.0, 6.0-6.5 and 7.0-7.5 for Cd(II), Cu(II), Pb(II) and Zn(II) respectively. Under these conditions there was 80% removal for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
100
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 271 publications
(124 citation statements)
references
References 38 publications
16
100
1
2
Order By: Relevance
“…These results showed that both Alternaria alternata and Penicillium aurantiogriseum are suitable for using as cadmium and mercury accumulators in wastewater. Similar results with respect to biosorption of cadmium and other heavy metals by fungi and bacteria have been reported earlier (Chang et al, 1997;Puranik and Paknikar, 1999;Costa et al, 2001;Pardo et al, 2003;Kefala et al, 1999;Ghoslan et al, 1999;Say et al, 2001;Watanabe et al, 2003;Ozdemir et al, 2004;Ayangbenro, and Babalola, 2017). Kumar et al, (2014) 2.55 mg/g of Cr respectively.…”
Section: Heavy Metals Concentrationssupporting
confidence: 88%
“…These results showed that both Alternaria alternata and Penicillium aurantiogriseum are suitable for using as cadmium and mercury accumulators in wastewater. Similar results with respect to biosorption of cadmium and other heavy metals by fungi and bacteria have been reported earlier (Chang et al, 1997;Puranik and Paknikar, 1999;Costa et al, 2001;Pardo et al, 2003;Kefala et al, 1999;Ghoslan et al, 1999;Say et al, 2001;Watanabe et al, 2003;Ozdemir et al, 2004;Ayangbenro, and Babalola, 2017). Kumar et al, (2014) 2.55 mg/g of Cr respectively.…”
Section: Heavy Metals Concentrationssupporting
confidence: 88%
“…The accumulation of heavy metals by B. anthracis PS2010 was found to be decreased by increasing the temperatures to 45°C, these results agree with the results obtained by Mameri et al (1999), Prescott et al (2002) and Uslu and Tanyol (2006). The pH value is one of the main factors in the biosorption efficiency and binding to microorganisms (Babich and Stotzky, 1985;Lopez et al, 2000;Jalali et al, 2002;Pardo et al, 2003). Results indicate that pH 8 was optimum for Cd 2+ , Co 2+ and pH range 7-8 was the optimum for Cu 2+ uptake.…”
Section: Resultssupporting
confidence: 88%
“…For pH values higher than the optimum values, the retention decreases again because of the formation of hydroxylated complexes of the metal. 26 …”
Section: Effect Of the Phmentioning
confidence: 99%